An evaluation of a teaching package constructed using a Web-based lecture recorder - Judith Segal (Association for Learning Technology, 1997)
This paper reports on an evaluation of a teaching package constructed using Audiograph, a Web-based lecture recorder developed at the University of Surrey. Audiograph is described in detail in Jesshope and Shafarenko (1997). Its developer aims to provide a medium by which multimedia teaching packages, based on traditional university lectures, may be developed rapidly by the lecturer(s) concerned (as opposed to professional CAL developers) at low cost. Audiograph is designed so that development time should only be in the order of two hours for every hour of presentation. Packages developed using Audiograph make much use of audio, which is somewhat unusual (apart from in video clips) in a package not dedicated to Computer-Assisted Language Learning or to addressing learning difficulties associated with vision. They also use text and (some) animation.